2017
DOI: 10.1128/jcm.00300-17
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Group B Streptococcus Capsule Type by Use of a Dual Phenotypic/Genotypic Assay

Abstract: The group B streptococcus (GBS) capsular polysaccharide (CPS) is an important virulence factor which is also used for GBS typing. There are 10 CPS types (Ia, Ib, and II to IX). GBS that do not phenotypically type are considered nontypeable. All genes required for CPS synthesis are found on the GBS cps operon, which contains a highly variable CPS-determining region (cpsG-cpsK). The objective of this study was development of an assay to detect sialic acid on the GBS cell surface, followed by a genotypic PCR CPS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 76 publications
0
16
0
Order By: Relevance
“…Knowing that the presence of surface sialic acid can predict the presence of polysaccharide capsule, it was unusual to find in our collection three GBS isolates (PLGBS16, PLGBS17, and PLGBS18) which failed to react with antisera raised against the nine known CPS types (Ia, Ib, and II–VIII) yet were sialic acid positive 23 (data not shown). Additionally, these three isolates could not be genotyped by our previously described RT-PCR typing assay (which includes Ia, Ib, and II–IX) 23 , suggesting novel mechanisms of encapsulation. A polysaccharide stain revealed that these three GBS isolates microscopically displayed CPS surrounding the cell wall (Supplemental Figure 3 ).…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…Knowing that the presence of surface sialic acid can predict the presence of polysaccharide capsule, it was unusual to find in our collection three GBS isolates (PLGBS16, PLGBS17, and PLGBS18) which failed to react with antisera raised against the nine known CPS types (Ia, Ib, and II–VIII) yet were sialic acid positive 23 (data not shown). Additionally, these three isolates could not be genotyped by our previously described RT-PCR typing assay (which includes Ia, Ib, and II–IX) 23 , suggesting novel mechanisms of encapsulation. A polysaccharide stain revealed that these three GBS isolates microscopically displayed CPS surrounding the cell wall (Supplemental Figure 3 ).…”
Section: Resultsmentioning
confidence: 87%
“…The relevant characteristics of the bacterial strains used in this study are listed in Table 4 . We reported previously that 159/1683 GBS isolates collected from patients between 2003 and 2013 were identified as NT 31 and of those, 84 of the 159 were sialic acid negative (sia(−)) 23 , whereas 75/159 were sialic acid positive (sia(+)) 23 . Of the 75 serologically nontypable sia(+) isolates, only three isolates (PLGBS16, PLGBS17, and PLGBS18) could not be genotyped by our previously described RT-PCR typing assay (which included Ia, Ib, and II–IX) 23 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations